(untitled) (Annals of Medical Research, 2023)
Aim: Kidney transplantation is the most optimal end stage renal disease (ESRD) treatment. It is more advantageous treatment regard to both its effect on the patient’s life quality or mortality. The number of patients who underwent or followed after renal transplant is constantly increasing while their survival becomes a topic more frequently. Different centers therefore report different survival rates in the post-transplantation process. In this study, the transplantation progress and the functional graft survival rates of the patients who have received renal transplants and are followed in our center and the factors which influence the survival rates are explored. Materials and Methods: The patients over 18 years old who applied to Inonu University Turgut Ozal Medical Center Nephrology Department Policlinics who received transplants retrospectively analyzed. Results: While the median for the functional graft period of the patients were 60 months, the longest was found to be 240 months. The grafts of our 77% patients are functional, while 3.7% are exitus with functional graft due to various reasons. 5.3% of the patients received HD again, 3% started PD and 1.3% underwent retransplantation. Conclusion: While the number of transplants are increasing day by day in Turkey, studies on the long term functional graft survival results and the patients’ pre- and post-transplant characteristics are limited and there is not much literature data related to Turkey. We aimed to contribute to the literature with our data. Also, the duration of ESRD increases, the lower is the functional graft time significantly. The preferred ESRD treatment should, therefore, be renal transplantation. Renal transplants could be preferred in suitable patients or donors of advanced age, and transplant age spectrum could be extended.